Infrared Spectra Investigation of CuO-Al[2]O[3] Precursors Produced by Electrochemical Oxidation of Copper and Aluminum Using Alternating Current; Key Engineering Materials; Vol. 712 : Advanced Materials for Technical and Medical Purpose (AMTMP 2016) - Usoltseva N. V. Natalia Vasilievna; Korobochkin V. V. Valery Vasilievich; Dolinina A. S. Alesya Sergeevna; Ustyugov A. M. Alexander (Electrophysical and Electrochemical Methods and Technologies of Materials Treatment, 2016)
Title screen